Determination of optimum area of specimen for NRC test in 28 m reverberant room - 389936 Wan Hafidzi Yunus (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik - Telekomunikasi)) - Universiti Teknologi Malaysia, 2006